2020
DOI: 10.1111/bju.15160
|View full text |Cite
|
Sign up to set email alerts
|

Survival following cytoreductive nephrectomy: a comparison of existing prognostic models

Abstract: Objective To validate models currently used to predict metastatic renal cell carcinoma (mRCC) outcomes in a cohort of patients undergoing cytoreductive nephrectomy (CN). Patients and methods A total of 10 RCC prognostic models (International Metastatic RCC Database Consortium [IMDC]; Memorial Sloan Kettering Cancer Center [MSKCC]; Culp; Leibovich; University of California at Los Angeles Integrated Staging System [UISS]; Stage, Size, Grade, and Necrosis [SSIGN]; Yaycioglu; Karakiewicz; Cindolo; and Margulis) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…A key study by Westerman et al found that commonly used 10 RCC prognostic models have limited discriminatory capacities and are inadequate for risk stratification. 47 Therefore, given that SLC7A11 was identified as an independent prognostic factor in RCC and was able to contribute to clinical benefit (Figure 3C-E), introducing SLC7A11 into the traditional prognostic model will improve its accuracy. In addition, patients with high SLC7A11 expression were prone to recurrence and progression (Figure 6H).…”
Section: Discussionmentioning
confidence: 99%
“…A key study by Westerman et al found that commonly used 10 RCC prognostic models have limited discriminatory capacities and are inadequate for risk stratification. 47 Therefore, given that SLC7A11 was identified as an independent prognostic factor in RCC and was able to contribute to clinical benefit (Figure 3C-E), introducing SLC7A11 into the traditional prognostic model will improve its accuracy. In addition, patients with high SLC7A11 expression were prone to recurrence and progression (Figure 6H).…”
Section: Discussionmentioning
confidence: 99%
“…Their respective prognoses for around 23% of patients in a treatment-naïve cohort undergoing the first line of targeted therapy do not match, suggesting limited prognostic capacity (Okita et al, 2019). They also do not perform well in predicting OS in patients undergoing cytoreductive nephrectomy (Westerman et al, 2020). Thus, implementation of additional or new biomarkers, to reliably stratify RCC patients in the era of targeted therapies, might be beneficial.…”
Section: Comparison To Current Standardsmentioning
confidence: 99%
“…Patient selection is also a crucial consideration when evaluating the benefits of CN ( 41 ). As an invasive procedure for patients with high disease burden, CN carries a higher mortality risk than standard nephrectomy for T1 or T2 renal tumors ( 42 ).…”
Section: Discussionmentioning
confidence: 99%